If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + -12 = 11 + -4n Reorder the terms: -12 + 4n = 11 + -4n Solving -12 + 4n = 11 + -4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '4n' to each side of the equation. -12 + 4n + 4n = 11 + -4n + 4n Combine like terms: 4n + 4n = 8n -12 + 8n = 11 + -4n + 4n Combine like terms: -4n + 4n = 0 -12 + 8n = 11 + 0 -12 + 8n = 11 Add '12' to each side of the equation. -12 + 12 + 8n = 11 + 12 Combine like terms: -12 + 12 = 0 0 + 8n = 11 + 12 8n = 11 + 12 Combine like terms: 11 + 12 = 23 8n = 23 Divide each side by '8'. n = 2.875 Simplifying n = 2.875
| 15x+8y=131 | | -131=-3-4(8-3v) | | a-20=17 | | -3m+4=-2m-5 | | 12=10y-8y | | x-7=3(x-4) | | 6-x=3(x+10) | | 10b+8b=360 | | 3075=37.5a | | 6x^2+36x+192=0 | | 5x-12=9x+5 | | 3(x+2)+1=2x-8+x+13 | | -16=2a-6a | | 637=13a | | x^2=-2+15 | | 5z=1.7+4.3 | | f(x)=6x^2+36x+192 | | x+37=129 | | 4+(m/5)=6 | | -5n-8-56m=-8 | | 4x^2+9=2x^2+3(5x+3) | | (2x^2)-(1x)-24=0 | | 12h^2-31h+20= | | 3(2x-5)=18 | | x^6+7x^3+64=0 | | 6x=6x-9 | | 3(m+3)-16= | | 36=13w-4w | | X+2=289 | | 10x=-4x+-7 | | -mn+7mp+10m=-2n-8 | | 3a^2+9a+30=0 |